A Pandemic Federal Election: Democracy Under Conditions of Emergency - Pal, Michael (Ottawa Law Review / Revue de droit d’Ottawa)

(untitled) (Ottawa Law Review / Revue de droit d’Ottawa, 2021)
The challenge of administering free and fair elections in the midst of a pandemic where any mass event raises obvious risks of transmission of the virus has generated considerable controversy around the globe. Jurisdictions have adopted diverse strategies in their attempt to balance the need for elections and public health and safety. This article assesses the main legal issues raised by the prospect of conducting a federal election in Canada during the pandemic. In sum, I argue for new measures at polling stations to ensure public health, expanded advance voting, and, where ballots are mailed-in, accepting all that are postmarked by election day. Implementing some of these reforms would require legislative amendment. Passing amendments in a timely fashion may be a challenge, however, in a minority Parliament that is justifiably occupied with urgent matters related to the pandemic and with limited sitting hours in the midst of an experiment with virtual proceedings. Parliament should urgently turn its mind, however, to the likelihood of a pandemic election and what reforms are needed.Section II discusses the legal framework for conducting elections during an emergency. In sum, the regular rules in the Canada Elections Act largely continue to apply and are not displaced by either emergency legislation or special provisions in the Act itself. Section III summarizes and analyzes the current options for casting a ballot in federal elections, in light of the likely constraints and threats posed by the pandemic. Section IV takes a deep dive into in person voting during a pandemic. It discusses in particular changes within polling stations to adapt to the pandemic and the expansion of early voting opportunities. Section V analyzes the pressing topic of mail-in voting. I argue that the existing system for voting by mail appears likely to be inadequate if used on a much wider scale than in previous elections, when few votes were cast in that fashion. Voter education should be a priority in response to some of the features of voting by mail. Legislative reforms are also needed, however, to ensure that all votes cast by election day and received within a reasonable timeframe are properly counted.